Protic Ionic Liquid as Reagent, Catalyst, and Solvent: 1‐Methylimidazolium Thiocyanate. (26th February 2021) - Andreev, Ivan A.; Ratmanova, Nina K.; Augustin, André U.; Ivanova, Olga A.; Levina, Irina I.; Khrustalev, Victor N.; Werz, Daniel B.; Trushkov, Igor V.
Abstract: We propose a new concept of the triple role of protic ionic liquids with nucleophilic anions: a) a regenerable solvent, b) a Brønsted acid inducing diverse transformations via general acid catalysis, and c) a source of a nucleophile. The efficiency of this strategy was demonstrated using thiocyanate‐based protic ionic liquids for the ring‐opening of donor‐acceptor cyclopropanes. A wide variety of activated cyclopropanes were found to react with 1‐methylimidazolium thiocyanate under mild metal‐free conditions via unusual nitrogen attack of the ambident thiocyanate ion on the electrophilic center of the three‐membered ring affording pyrrolidine‐2‐thiones bearing donor and acceptor substituents at the C(5) and C(3) atoms, respectively, in a single time‐efficient step. The ability of 1‐methylimidazolium thiocyanate to serve as a triplex reagent was exemplarily illustrated by (4+2)‐annulation with 1‐acyl‐2‐(2‐hydroxyphenyl)cyclopropane, epoxide ring‐opening and other organic transformations. Abstract : A resplendent trio: Protic ionic liquids (PILs) with nucleophilic anions served in concert as regenerable reaction medium, Brønsted acid, and a source of nucleophile. Heating of donor–acceptor cyclopropanes with 1‐methylimidazolium thiocyanate (B:⋅HNCS) afforded products of formal (3+2)‐ and (4+2)‐cycloaddition of isothiocyanic acid.